2011
DOI: 10.7863/jum.2011.30.10.1351
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of Partial-Thickness Tears of the Distal Triceps Brachii Tendon

Abstract: Partial-thickness distal triceps brachii tendon tears have a characteristic appearance with selective superficial tendon retraction and olecranon enthesophyte avulsion fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…Ultrasound is performed with the elbow in flexion and shows reduced echogenicity and occasional calcification in tendinopathy. Partial tears of the superficial or deep insertion of the triceps can also be readily seen [61,62].…”
Section: Investigationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasound is performed with the elbow in flexion and shows reduced echogenicity and occasional calcification in tendinopathy. Partial tears of the superficial or deep insertion of the triceps can also be readily seen [61,62].…”
Section: Investigationsmentioning
confidence: 99%
“…Downey et al reported on the ultrasound findings of partial thickness tears [62]. They identified 30 tears of which five underwent surgical intervention.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The muscle bellies form a single thick tendon inserting on the proximal portion of the olecranon process of the ulna. The distal triceps brachii inserts as two tendons, a superficial tendon composed of the lateral and long heads, and a deeper medial head (28,(30)(31)(32). Both tendons share a common insertion (28,(30)(31)(32).…”
Section: Triceps Tendonmentioning
confidence: 98%